A METHOD FOR DETERMINING 1,4-BENZOTHIAZINE DERIVATIVES IN RAT PLASMA BY HPLC AND ITS APPLICATION TO A PHARMACOKINETIC STUDY - Rai, Amit; Raj, Vinit; Singh, Ashok K.; Keshari, Amit K.; Saha, Sudipta (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The objective of the study was to develop, optimize and validate of a new reverse-phase high-performance liquid chromatography (RP-HPLC) method for the determining 1,4-benzothiazine derivatives (AR13 and AR15) in a biological sample of rat plasma. The 1,4-benzothiazine derivatives are produced by the synthetic reactions. Methods: RP-HPLC separation was performed using an ODS-2 Hypersil column with gradient elution mobile phase consisting of water-acetonitrile for AR13 and AR15 (1:9 v/v, 3:7 v/v) at room temperature 1 ml/min flow rate, and interfaced with photodiode array detector (PDA) detector, 233 nm, 235 nm respectively. Results: A linear response was obtained between (range from 0.100-10.00 mg/ml) AR13 and (range from 0.096–9.88 mg/ml) AR15 with correlation coefficient 0.999 and 0.998. The linearity range of both AR13 and AR15 was 101.65±1.5 and 98.78±1.7. Conclusion: It was concluded that the method was simple, accurate, sensitive, accurate and reproducible and has been successfully applied to the pharmacokinetic study of AR13 and AR15 in rat plasma.